THEORETICAL FOUNDATIONS OF THE "GREEN ECONOMY" - Yormatov Sh.; Nurmuratova Nozima (The Conference Hub, 2025)
Green economy, Green jobs and Green growth are the buzzwords of the current times. The increased emission of carbons and the consequent loss of economic and social welfare are the concerns of both the national and international development agencies in recent years. It has created awareness among the people the need to protect the environment. The UN Millennium Development Goals and Sustainable Development Goals have also reiterated the importance of green economy. But, the transition from the existing accustomed economic growth models to a green growth model is not easy to attain. When we look at the principles of green economic model, one can see that it envisions the various aspects of economic, environmental and social principles. The economic dimension of green economy is based on the principles of recognition of natural capital and values, promotes resource efficiency and creates decent work and green jobs. The environment dimension of green economy relies on the principles of protection of biodiversity and ecosystems, respects planetary boundaries and ecological limits and promotes international environmental sustainability goals. Coming to the principles of social aspects, green economy envisions poverty reduction, well-being, livelihoods, social protection and access to essential services. Above all, the concept is equitable, fair and just-between and within countries and between generations. This paper is a modest attempt to review the conceptual cobwebs of the green economy concept with a view to create a sense of the need of a new growth model.
Keywords: Brudtland Report, Climate Change, Green Economy, Sustainable Development.